Obese patients exhibit a greater enhancement in mental health-related quality of life compared to non-obese patients following thoracoscopic ablation of atrial fibrillation - Meulendijks, Eva R.; Roelofs, Manouck J. M.; de Vries, Tim A. C.; Wesselink, Robin; Al-Shama, Rushd F. M.; van Boven, Wim-Jan P.; Driessen, Antoine H. G.; Berger, Wouter R.; de Jong, Jonas S. S. G.; de Groot, Joris R. (Frontiers in Cardiovascular Medicine, 2025)
BackgroundObesity is an important risk factor for atrial fibrillation (AF) development and progression. Furthermore, obesity reduces health-related quality of life (HRQoL), an essential indicator for treatment efficacy of AF ablation. Nevertheless, the extent to which obesity influences changes in HRQoL and the recurrence of AF following ablation, especially thoracoscopic AF ablation, remains largely unexplored.AimsWe assessed in obese vs. non-obese patients undergoing thoracoscopic AF ablation: (1) HRQoL upon ablation, (2) AF recurrence incidence, (3) the association between recurrence incidence and HRQoL.Methods & results408 prospectively enrolled patients were included for analysis. Heart rhythm was systematically monitored during follow-up. AF recurrence was defined as any atrial tachyarrhythmia episode > 30 s. HRQoL and recurrence incidence were assessed for normal weight (BMI ≤ 24.9 kg/m2), overweight (25.0–29.9 kg/m2) and obese (≥30.0 kg/m2) patients. HRQoL was assessed at baseline and 1-year follow-up. Obese patients scored lower in pre-operative HRQoL across 6/8 subscales vs. non-obese patients (p < 0.01–0.05). While HRQoL increased in all patients, obese patients showed a trend towards an even greater improvement of mental HRQoL (p = 0.07) vs. non- obese patients. In obesity, mental HRQoL increased similarly for those with and without AF recurrence (p = 0.78), whereas in non-obese patients, AF recurrence was associated with less improved mental HRQoL (p = 0.03). AF recurrence at 1-year was similar between all weight groups (72.4%, 68.0%, 70.4%, p = 0.69).ConclusionsAfter thoracoscopic ablation, obese patients experience a comparable incidence of AF recurrence as non-obese patients. Interestingly, obese patients also exhibit a more significant enhancement in mental quality of life, regardless of whether AF recurs or not.